Species of Lissothrips and Williamsiella from mosses and lichens in Australia and New Zealand (Thysanoptera, Phlaeothripinae) - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2015)
Species of Lissothrips and Williamsiella live in association with mosses and lichens. Their gut contents are commonly blue-green, suggesting that they possibly feed on blue-green algae. Three species of Lissothrips are known from New Zealand, of which two are here recorded from Australia together with six new species. Williamsiella is recorded from Australia for the first time, with one new species.